Molecular characterization of invasive Neisseria meningitidis isolates collected in Lithuania (2009-2019) and estimation of serogroup B meningococcal vaccine 4CMenB and MenB-Fhbp coverage - Sereikaitė, Emilija; Plepytė, Rūta; Petrutienė, Aurelija; Stravinskienė, Dovilė; Kučinskaitė-Kodzė, Indrė; Gėgžna, Vilmantas; Ivaškevičienė, Inga; Žvirblienė, Aurelija; Plečkaitytė, Milda (Frontiers in Cellular and Infection Microbiology, 2023)
Neisseria meningitidis causes invasive meningococcal disease (IMD), which is associated with significant mortality and long-term consequences, especially among young children. The incidence of IMD in Lithuania was among the highest in European Union/European Economic Area countries during the past two decades; however, the characterization of meningococcal isolates by molecular typing methods has not yet been performed. In this study, we characterized invasive meningococcal isolates (n=294) recovered in Lithuania from 2009 to 2019 by multilocus sequence typing (MLST) and typing of antigens FetA and PorA. The more recent (2017-2019) serogroup B isolates (n=60) were genotyped by analyzing vaccine-related antigens to evaluate their coverage by four-component (4CMenB) and two-component (MenB-Fhbp) vaccines using the genetic Meningococcal Antigen Typing System (gMATS) and Meningococcal Deduced Vaccine Antigen Reactivity (MenDeVAR) Index methods, respectively. The vast majority (90.5%) of isolates belonged to serogroup B. MLST revealed a predominance of clonal complex 32 (74.02%). Serogroup B strain P1.19,15: F4-28: ST-34 (cc32) accounted for 64.1% of IMD isolates. The overall level of strain coverage by the 4MenB vaccine was 94.8% (CI 85.9-98.2%). Most serogroup B isolates (87.9%) were covered by a single vaccine antigen, most commonly Fhbp peptide variant 1 (84.5% of isolates). The Fhbp peptides included in the MenB-Fhbp vaccine were not detected among the analyzed invasive isolates; however, the identified predominant variant 1 was considered cross-reactive. In total, 88.1% (CI 77.5-94.1) of isolates were predicted to be covered by the MenB-Fhbp vaccine. In conclusion, both serogroup B vaccines demonstrate potential to protect against IMD in Lithuania.